Jogo para o ensino de probabilidade - Assumpção, Rosangela Aparecida Botinha (2023)
The use of emerging technologies in the educational context brings huge challenges and possibilities for the classroom. In this sense, we have games, which are presented as an alternative for 21st century education through an interactive and creative environment. This work proposes a multi-player computer game for learning, with the aim of motivating students and consequently encouraging the study of probability. The proposed game, called CombinaDado, works with the contents of Simple Probability and Conditional Probability using two virtual dice. In this game, students are players who try to earn points by hitting probability challenges defined by a central application running on a computer and presented by a Datashow. Students answer the challenges using a mobile application on their cell phone. Thus, this work focuses on the design of these applications. It is expected that this game can contribute to the teaching of probability, encouraging teachers and students to a more active learning methodology.